Análise comparativa das instituições privadas de ensino: estudo sobre as matrizes curriculares dos cursos de Ciências Contábeis do Estado de São Paulo com maior aprovação no exame de suficiência do Conselho Federal de Contabilidade - Silva, Euclides Bezerra da (2019)
The Entities need Accountants qualified to generate information and to give support for users in the decisions-making. Therefore, this research aimed to conduct a comparative study of curricular matrices of the five (5) Private Higher Education Institutions of the State of São Paulo, which most approved the sufficiency exam in 2017. For the accomplishment, exploratory and qualitative research was used, demonstrating its similarities and differences. The results demonstrated that the selected HEIs apply in their contents of the course of accounting sciences, an hourly load above 3000 hours of classes, higher than the requirement of the Ministry of Education and Culture (MEC), varying between 8% and 47%. Another relevant result, it was that four (4) of five (5) HEIs analyzed investing between 13% and 48% above the curriculum matrix adjusted by CFC, in the group – basic formation content, giving a solid base for the student initial formation in the academic life, resulting in greater ease of understanding in the other disciplines. Besides that, all the HEIs of this study investing in differential contents as: sociology, psychology among others. Finally, it was observed the adjusted curriculum matrix proposed by the CFC, approve more than 50% (fifty percent) of the candidates that take the sufficiency exam. It is hoped that this model presented can become a benchmarking, improving the teaching of accounting throughout the country